Human Capital and Economic Growth 2019
DOI: 10.1007/978-3-030-21599-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Health and Income: Theory and Evidence for OECD Countries

Abstract: In this chapter we examine whether the Solow growth model is consistent with the international variation in the standard of living once investments in education and health are explicitly and simultaneously taken into account. Using the sample of OECD countries, we provide evidence that the level of per capita income is positively affected by the population's health level, here proxied by the life expectancy at birth. Public expenditure on health affects indirectly the level of per capita income through its pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 105 publications
0
5
0
2
Order By: Relevance
“…Income is a description of the level of a person's ability to fulfill his material needs in a certain time unit, usually per month. Income is used for two purposes, namely for consumption expenditure (purchase of goods and services) and for saving in financial institutions [6]. Community income can be in the form of salaries, wages, rent, and profits received from productive services.…”
Section: Incomementioning
confidence: 99%
See 1 more Smart Citation
“…Income is a description of the level of a person's ability to fulfill his material needs in a certain time unit, usually per month. Income is used for two purposes, namely for consumption expenditure (purchase of goods and services) and for saving in financial institutions [6]. Community income can be in the form of salaries, wages, rent, and profits received from productive services.…”
Section: Incomementioning
confidence: 99%
“…Revenue is recognized after the production process is followed by the sales process. The income given by the service users is obtained from the sale of production goods purchased by the public, calculated quantitatively between the difference between production costs and sales [6].…”
Section: Incomementioning
confidence: 99%
“…Fokus utama pembangunan manusia adalah memberikan kesempatan sumber daya manusia untuk tumbuh dan menikmati hidup yang produktif, sehat, dan berumur panjang (BPS, 2021). Beberapa kajian menggunakan variabel indeks pembangunan manusia sebagai tujuan dari proses pembangunan (Alatas & Cakir, 2016;Bucci et al, 2019;Ezkirianto & Alexandi, 2018;Pelinescu, 2015). Sementara itu, variabel pertumbuhan ekonomi digambarkan sebagai proksi yang tidak sempurna untuk menilai kesejahteraan, atau sebagai sarana dalam mengembangkan pembangunan manusia (Pelinescu, 2015).…”
Section: Pendahuluanunclassified
“…At the macroeconomic level, this relationship can be explained by the impact of health on the three main drivers of growth: labor productivity, human capital accumulation and total factor productivity (TFP). GEH can improve health outcomes and lead to higher labor productivity (Bucci, Carbonari, & Trovato, 2019;Rivera & Currais, 1999;Sengupta, 2017;Wahab & Kefeli, 2017). A study by Culyer and Wagstaff (1993) found that a 10% increase in GEH was associated with a 0.5% increase in labor productivity.…”
Section: Theoretical Studiesmentioning
confidence: 99%